Stranded steel wire ropes Part 2. Specification for ropes for general purposes - British Standards Institution (London BSI, 1987)
Ropes, Wire ropes, Steel-wire ropes, Strands, Design, Cores (ropes), Rope pitch, Breaking load, Diameter, Weight (mass), Tensile strength, Grades (quality)
Replaced By BS EN 12385-4:2002+A1:2008
Superseded, Withdrawn
Cross References BS 2763, BS 5750:Part 2, BS 6570, ISO 4344
Replaces BS 302:1968, BS 3530:1968
Keywords: Steel-Wire Ropes -- Standards